Factors Influencing Employee Engagement At Top Glove Sdn Bhd - Yamunaa, Kalaiarasu (2024)
The objectives of this research was to examine the relationship between well-being, training and career development, work culture and compensation & benefits towards employee engagement at Top Glove Sdn Bhd. Social Exchange Theory (SET) was used in this study to utilized in developing the research framework. Sampling about 108 of respondents were participated in this study and data were collected through questionnaire. The four hypotheses were tested by four analysis using SPSS 2.0. The findings indicated that well-being, training and career development, work culture and compensation & benefits were significantly related to employee engagement. The findings of this research will be very helpful for Top Glove Sdn Bhd, Human Resource Management, Researchers, Policy Makers and Students. Theoretical and practical implications of the study as well as suggestions for future research were discussed.